Pengembangan Perangkat Pembelajaran Berbasis Masalah yang Mengacu pada Learning Trajectory dan Berorientasi pada Kemampuan Justifikasi Matematis Siswa - Alvi Khoirunnisak; Ilham Rizkianto (IKIP Siliwangi, 2020)
The present research and development project aims to develop and describe the quality of learning material consisting of lesson plans and student worksheets to facilitate students mathematical justification skills. The learning material is based on problem-based learning (PBL) approach and learning trajectory on the Cartesian Coordinate System. This project uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subject of this research is 32 students in VIIIC SMPN 2 Bambang Lipuro. Based on the result of the validation assessment, the lesson plan and student worksheets are very valid. Based on the result of practicality using a student questionnaire, the learning material is practical. Based on the result of practicality using the observation sheet of learning implementation, the learning material is very practical. Based on the effectiveness assessment using the students mathematical justification skill test, 75% of students have minimum mathematical justification skills in the good category. However, based on the z-test, the learning material is not effective because zcount = 0,6172 < zα =1,654. So, the learning material is valid and practice to be implemented, but not yet effective to facilitate student’s justification skills. It was possibly due to obstacles happening during the implementation, like the implementation of PBL needs more time than it planed, and some students did not do the writing task.Keywords: learning material, PBL, learning trajectory, mathematical justification skills